Characteristics of Customary Law and Its Characteristics - Aziz Siregar (Journal of Adat Recht, 2024)
In today's sophisticated era we sometimes forget the background of the birth of the law that we know in the social life environment in Indonesia and other Asian countries such as Japan as a country that is almost the same in ideological settings, namely the existence of sources where legal regulations are not written and growing and developing and maintained with the customs adopted by the community as a reference and guideline in step The background in the preparation of this paper is first to understand the terms and application of customary laws and habits in society as an implementation of social and kinship in society. Especially the Indonesian people who are still very strong today even become guidelines that cannot be separated from the current law